The steric effect of benzodifuran based polymers via alkyl side chain manipulation: a simple approach for enhancing the photovoltaic performance. (9th December 2021) - Gao, Pan-Feng; Wang, Li-Yong; Fu, Hai-Yan; Zhang, Jian-Yi
Abstract : A series of narrow band gap conjugated copolymers with different alkyl side chains were synthesized via Stille copolymerization of benzodifuran (BDF) and benzothiadiazole (BT) monomers. Abstract : A series of narrow band gap conjugated copolymers with different alkyl side chains were synthesized via Stille copolymerization of benzodifuran (BDF) and benzothiadiazole (BT) monomers. The origination effect of the alkyl side chains, linked to the thienyl side groups of BDF based backbone, on the optical, electronic and morphological properties of the resulting polymers were investigated and correlated with the photovoltaic performance. It was found that the different alkyl side chains positions have a significant impact on the polymeric optoelectronic properties due to differences of torsion in the backbones. The best performance of the bulk-heterojunction solar cells (BHJ) with a power conversion efficiency (PCE) of 6.73% was achieved with PBFDBT- o as the donor and (6, 6)-phenyl-C71 -butyric acid methyl ester (PC71 BM) as the acceptor, which can be attributed to its higher charge carrier mobility as well as the optimized interpenetrating network with respect to the other two polymers. The results demonstrated that the alkyl side chain position manipulations play a crucial role in adjusting the optoelectronic properties of BDF based copolymers and it is a promising molecular design strategy for the application of solar cells.